Analisis Pemasaran Dalam Era Digital : Tantangan Dan Peluang - Allya Ega Annisa Hutauruk; Selvia Santa Maria Siallagan; lidya Mutiara Hutasoit; Aurora Elise Putriku; Lenti Susana Saragih (Akuntansi, 2024)
Marketing in the digital era has presented new challenges and opportunities for marketing practitioners. These challenges include managing complex consumer data, increasingly fierce competition in the digital realm, and rapid changes in consumer behavior. However, amidst these challenges there are also opportunities to optimize the use of technology and digital platforms to increase marketing effectiveness, expand market reach and strengthen interactions with consumers. This article will discuss several key challenges faced by marketing practitioners in the digital era as well as opportunities that can be utilized to overcome these challenges.